Pengaruh Model Pembelajaran Teaching Factory Terhadap Kemampuan Kreativitas Belajar Siswa pada Mata Pelajaran Pemeliharaan Mesin Sepeda Motor Kelas XII TSM SMK Negeri 7 Lhokseumawe - Muhammad Fathur Rosi; Abubakar Abubakar; Nuraina Nuraina (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to obtain information about the learning creativity of students of SMK Negeri 7 Lhokseumawe in the subject of motorcycle engine maintenance using the teaching factory learning model. This study was conducted at SMK Negeri 7 Lhokseumawe. This study uses a quasi-experimental design with a quantitative approach using 2 samples, namely class XII TSM-1 as the experimental class and class XII TSM-2 as the control class, where the samples taken in this study used a purposive sampling technique. The instrument in this study was a questionnaire in the form of a statement given after learning the teaching factory model in the experiment. Data analysis was carried out using a non-parametric test. Based on the results of the questionnaire on students' learning creativity abilities, the average value of the experimental class was 144.31 with a standard deviation of 11.068 and the average value of the control class was 127.47 with a standard deviation of 10.834. Based on the criteria of the non-parametric test if the significant value is <0.05 then H0 is rejected. The results of the Mann Whitney test with a significant value of <0.05 on the experimental class value obtained an Asymp.sig.(2-tailed) value of 0.001, which means that the teaching factory learning model has a positive effect on students' learning creativity abilities in the subject of motorcycle engine maintenance.